2018
DOI: 10.1097/inf.0000000000001816
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Antimicrobial Prescribing and Outcomes in Pediatric Complicated Appendicitis

Abstract: Complicated appendicitis is an important target for antimicrobial stewardship and quality improvement efforts. A condition-specific CPG can improve both antimicrobial utilization and clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 23 publications
2
21
0
Order By: Relevance
“…Time without fever was one of the most common discharge criteria. The required period without fever ranged between 12 and 72 hours . Only one small underpowered study explicitly excluded a body temperature value from their discharge criteria, with comparable complication rates and LOS reported .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Time without fever was one of the most common discharge criteria. The required period without fever ranged between 12 and 72 hours . Only one small underpowered study explicitly excluded a body temperature value from their discharge criteria, with comparable complication rates and LOS reported .…”
Section: Resultsmentioning
confidence: 99%
“…A significant reduction in LOS was achieved in eight studies (Table S4). Importantly, in all but one study these outcomes occurred with either comparable or improved rates of complication or readmission . Yousef et al and Willis et al notably reported reductions in intra‐abdominal abscess rate by approximately half.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations